Sistem Informasi Penjualan Barang Online dengan Menggunakan PHP & MySql di Tiara Toserba Kota Sukabumi - Nunik Yudaningsih (LP2M CBI Press, 2016)
Tiara Toserba Sukabumi City is a retail company that sells all kinds of needs such as clothes, shoes, groceries, household appliances, and so on. Tiara Toserba Sukabumi was established in 2000 and has worked with more than 100 companies. The system of selling goods at Tiara Toserba Sukabumi City is still manual, which means that prospective buyers must come directly and choose what items are needed.The sales system in this way only covers customers directly, even though not all potential customers can come directly to buy the goods they need due to time, weather, energy, and so on.The result of the research and design of this computer equipment sales information system is the availability of information about computer equipment products for consumers and consumerssimplify the implementation of the work system at Tiara Toserba Sukabumi using PHP and MySql with the aim of helping minimize sales process time in order to increase sales volume and value so that company income can increase.